Comparative analysis of early radiolucencies in cementless versus cemented total knee arthroplasty - Vadim Benkovich; Artsiom Abialevich; Vladislav Osinsky; Guy Benkovich (Bone & Joint Open)
Aims: This study aimed to compare early outcomes of cemented and cementless total knee arthroplasty (TKA). Methods: We analyzed 593 patients who underwent cemented or cementless TKA between January 2017 and December 2022. Data collected included demographics, BMI, comorbidities, surgical variables, follow-up duration, and outcomes such as implant survivorship, radiolucencies (assessed using the Modern Knee Society Radiographic Evaluation System (MKSRES)), short-term complications, revision rates, periprosthetic fractures, hospital length of stay, and readmissions. Results: The study included 593 patients, equally divided into cemented and cementless groups. Age (p = 0.354) and sex (p = 0.342) were similar, though BMI was higher in the cementless group (p < 0.001). Comorbidities were comparable. Radiolucencies and osteolysis occurred in 12 cemented and ten cementless cases, with no significant differences across femoral and tibial zones (p ≥ 0.479). All radiolucencies were stable, partial, and non-progressive. No cases of aseptic loosening required revision. Revisions for periprosthetic fractures were rare (p = 0.218). Hospital length of stay (p = 0.623) and readmissions (p = 0.216) were similar between groups. The mean follow-up time postoperatively was slightly longer in the cementless group (4.22 years (SD 0.84)) compared to the cemented group (4.01 years (SD 1.03)) (p < 0.001). Conclusion: Cemented fixation remains the gold standard in TKA due to its reliability, yet advancements in implant design and indications support increasing adoption of cementless TKA. This study found comparable early outcomes for both methods, with stable radiolucent lines and no aseptic loosening during follow-up. The MKSRES facilitates standard radiological assessment, enabling precise implant monitoring and improving TKA outcome evaluation. These findings support the equivalence of cemented and cementless fixation in early survivorship. Cite this article: Bone Jt Open 2025;6(6):707–714.